The Cambridge companion to postmodern theology - Vanhoozer, Kevin J. (Cambridge Cambridge University Press, 2005)
Postmodernity allows for no absolutes and no essence. Yet theology is concerned with the absolute, the essential. How then does theology sit within postmodernity? Is postmodern theology possible, or is such a concept a contradiction in terms? Should theology bother about postmodernism or just get on with its own thing? Can it?
Theology and the condition of postmodernity: a report on knowledge (of God) / Kevin J. Vanhoozer -- Anglo-American postmodernity: a theology of communal practice / Nancey Murphy and Brad J. Kallenberg -- Postliberal theology
Includes bibliographical references and index.
Keywords: Postmodern theology